THU0398 Secukinumab sustains individual clinical responses over time in patients with active ankylosing spondylitis: 2-year results from a phase 3 trial, measure 2. (15th June 2017) - Baraliakos, X; Schiff, M; Pavelka, K; Widmer, A; Porter, B; Gaillez, C
Abstract : Background: The assessment of achieving, maintaining or improving clinical response to biologics in ankylosing spondylitis (AS) is a part of treat-to-target recommendations aimed at optimising treatment goals. 1 Objectives: To evaluate patient (pt)-level secukinumab data and assess the likelihood of achieving, maintaining or improving an Assessment of SpondyloArthritis international Society (ASAS) response from Week (Wk) 2 (early response) to Wk 16 (primary endpoint) and from Wk 16 to Wk 52 or 104 (sustained effect) in pts with active AS from the MEASURE 2 trial. 2, 3 Methods: This is a post-hoc analysis of AS pts originally randomised to secukinumab 150mg (approved dose) who completed the 16-wk double-blind treatment period, followed by long-term uncontrolled treatment. Shift analyses on ASAS response between Wks 2 and 16 and Wks 16 and 52 or 104 were performed on subgroups of secukinumab 150mg treated pts categorised by their highest ASAS criteria response at the earlier time point (ASAS non-responder [ASAS NR], ASAS20 responder, ASAS40 responder) and evaluating whether this response was improved, sustained, or worsened at the later time point, based on observed analysis. Results: Overall, 65, 61 and 59 pts treated with secukinumab 150mg had available data to determine ASAS responses for shift analyses from Wk 2 to 16 and Wk 16 to 52 or 104, respectively. At baseline, mean age was 41.9±12.5 years, mean time since diagnosis was 7.0±8.2 years and mean Bath Ankylosing Spondylitis Disease Activity Index score was 6.6±1.5. Approximately half of the ASAS NR pts at Wk 2 or 16 subsequently developed an ASAS 20 or 40 response at the later time point of Wk 16 or 52, respectively. A total of 79% pts improved their response from ASAS20 to ASAS40 at Wk 16 (Wk 2 to 16) and another 44% pts improved their response from ASAS20 to ASAS40 from Wk 16 to 52. A majority (64% and 84%) of ASAS40 responders at Wk 2 or 16 maintained this response at Wk 16 or 52, respectively. Similar trends were observed in responses from Wk 16 to 104 (Figure). Conclusions: In this post-hoc pt-level analysis, the majority of secukinumab 150mg treated pts maintained or improved their ASAS responses over time, consistent with the sustainability of group-level ASAS responses reported previously. 2, 3 In particular, the majority of pts who achieved either an ASAS20 or ASAS40 response at Wk 2 or 16 maintained or improved their response at Wks 16, 52 or 104, respectively. References: Smolen JS, et al. Ann Rheum Dis 2014;73:6–16. Baeten D, et al. N Engl J Med 2015;373:2534–48. Marzo-Ortega H, et al. Ann Rheum Dis 2016;75:812–3. Disclosure of Interest: X. Baraliakos Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Werfen, Consultant for: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, Werfen, M. Schiff Consultant for: Abbvie, BMS, Lilly, J&J, Speakers bureau: Abbvie, K. Pavelka Speakers bureau: MSD, AbbVie, Roche, UCB, Amgen, Hospira, Egis, Pfizer, Medac, BMS, A. Widmer Shareholder of: Novartis, Employee of: Novartis, B. Porter Shareholder of: Novartis, Employee of: Novartis, C. Gaillez Shareholder of: Novartis, BMS, Employee of: Novartis